PERAN MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN DALAM KESIAPSIAGAAN BENCANA DI KOTA SEMARANG MENGGUNAKAN APLIKASI INARISK PERSONAL - Yuliyani, Dwi Nur; Harlistyarintica, Yora; Khoirunnisak, Anis (Journal of Democratia, 2024)
Disaster is a phenomenon in which a situation threatens people's lives. This is caused by natural factors and social factors so that it will result in many casualties, loss or loss of property, environmental degradation, and psychological impacts that will occur on society. According to Law Number 24 of 2007 concerning disaster classification in Indonesia. This classification concerns natural disasters, non-natural disasters and social disasters that are likely to occur around us.        The city of Semarang is at risk of natural disasters, especially tidal floods, landslides and drought. Due to its northern location which borders the Java Sea, as well as topographic conditions which are mostly hills, lowlands and coastal areas, it shows that there are various slopes and bulges which cause the Semarang City area to be potentially vulnerable to the threat of natural disasters.      This research uses a qualitative approach. By using data collection techniques used are in-depth interview techniques, observation and documentation. Data analysis used by the interactive model from Huberman and Miles includes data reduction, data presentation, and drawing conclusions.       The research results show that the role of students in Disaster Preparedness is very necessary because it makes it easier for the public to get updated data using the inaRISK Personal application in the event of disasters in Semarang City.  Then the researchers trained students to be able to fill out disaster reports in the inaRISK Personal program which can be applied to each student's smartphone.   Keywords: Role of Students, Disaster Preparedness, and Disaster Applications